2016
DOI: 10.1038/eye.2016.75
|View full text |Cite
|
Sign up to set email alerts
|

Change in choroidal thickness and the relationship with accommodation following myopic excimer laser surgery

Abstract: Purpose To investigate early changes in choroidal thickness (CT) and the relationship with accommodation after myopic excimer laser surgery. Methods We enrolled the right eye of 70 patients with myopia and without other ophthalmic or systemic diseases who were suitable for myopic excimer laser surgery. The CT was measured at the fovea and at distances of 0.5 and 2.5 mm for the following: nasal; temporal; superior; and inferior to the fovea preoperatively and at 1 month postoperatively. Other data collected inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…CT was observed thicker postoperatively [16], and there is research believing CT was affected by ciliary muscle contraction, which may explain why LT thickened. While in our research, results were similar, but not every measure point was statistically signi cant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CT was observed thicker postoperatively [16], and there is research believing CT was affected by ciliary muscle contraction, which may explain why LT thickened. While in our research, results were similar, but not every measure point was statistically signi cant.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, a slightly positive correlation between LT and sphere suggested that higher myopia had less AA, which may explain that some patients complained of accommodation hysteresis after surgery, especially in high myopia patients. The poor accommodative facility, slow accommodative responsiveness, and increased accommodation demand may attribute to the result [16].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a slightly positive correlation between LT and sphere suggested that severe myopia had less AA, which may explain that some patients complained of accommodation hysteresis after surgery, especially highly myopic patients. The poor accommodative ability, slow accommodative responsiveness, and increased accommodation demand may attribute to these results [16].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In addition to diseases, ocular surgeries such as vitrectomy, scleral buckling, myopic excimer laser surgery, and trabeculectomy cause changes in the thickness of choroid. [3][4][5][6] However, the data on the change in choroidal thickness after phacoemulsifcation cataract surgery are not clear. Some studies have reported an increase, 7 whereas others have reported no change in choroidal thickness.…”
mentioning
confidence: 99%